(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Introduction: hepatic hydatidosis (HH) or cystic echinococcosis (EC) is a zoonosis caused by Echinococcus ssp., characterized by the appearance of echinococcal cysts, mainly in the liver. The HH is classified as cystic, polycystic or alveolar echinococcosis according to the etiological agent. The final host is usually canids, which can contaminate intermediate hosts, such as humans, via oral-fecal route. From fecal eggs, oncospheres penetrate the circulatory system and deposit in the liver. The biological cycle continues until it causes infiltration in the liver parenchyma, and causes lesions called cysts, similar to a malignant neoplasm. Imaging and serological tests have been described for diagnostic aid. The clinical presentation is usually asymptomatic, for which conservative therapy is indicated, however in symptomatic and high systemic risk cases, the indication is surgical (ROSA et al., 2017). Objectives: analyze the clinical presentation of HH, discuss diagnostic and therapeutic approaches, and make it possible for health students. Material e métodos: literature review with articles from two databases. The Pubmed database used publications between 23/07/2018 and 23/07/2019 with the descriptor hepatic hydatidosis. The total number of findings was 14, of which 5 were excluded because they did not meet the study specificities. In the Scielo database, the descriptor hydatidosis was used. The total of results was 13, but only 5 were related to HH, and of these, 4 were discarded because they did not contain the necessary information. Results and discussion: the diagnosis was mainly made by serological and imaging tests, which depends on the degree of disease development. Shen et al. (2019) described the donut sign, heterogeneous mass with central necrosis and peripheral enhancement by fluorodeoxyglucose contrast on PET / CT imaging as a support factor for the diagnosis. Although, ultrasound is still the gold standard because it exhibits hepatic microvascular structures, which gives it accuracy and applicability. Once diagnosed, surgery is one of the main treatment forms, where a transverse abdomen block may be helpful. However, lobectomy is evidenced as more effective because it tends to reduce symptoms and systemic implications. Conservative drug choice as the first option has low therapeutic potential and symptoms maintenance. Some studies focus on the potential role of regulatory protein Foxp3 + Tregs, T cells, in the immune response against primary alveolar echinococcosis useful as a target for immunotherapy (WANG et al., 2018). Conclusion: the diagnosis of HH should be made by complementary exams due to nonspecific symptomatology. In addition, advantages were found in surgical intervention, which provided total relief of symptoms and systemic manifestations involution. The conservative approach was effective only to postpone surgical intervention.